Co-Infection of Hepatitis A and Hepatitis E Viruses in Outpatients in Dhaka, Bangladesh: A Case Series (East West Medical College Journal, 2025)
Hepatitis E Virus (HEV) and Hepatitis A Virus (HAV) infections continue to pose substantial global health concerns, especially in areas of insufficient sanitation and hygiene standards. This case series investigates the seroprevalence of Hepatitis A Virus (HAV) and Hepatitis E Virus (HEV) among two patients attending OPD of National Institute of Laboratory Medicine and referral center, Dhaka, Bangladesh. The findings underscore the importance of considering multiple hepatitis viruses in the diagnostic evaluation of patients with acute hepatitis symptoms, particularly in regions with variable prevalence rates for these pathogens.EWMCJ Vol. 13, No. 1, January 2025: 65-68